Earnings Management, Tax Avoidance, and Profitability Among MNC’s in Indonesia - Veronica, Angela; Lubis, Arief Wibisono (Syntax Corporation, 2024)
The study examines the influence of earnings management and tax avoidance on the profitability of parent multinational companies in Indonesia, except the financial sector, actively listed on the Indonesia Stock Exchange during the research period. The research period used in this study starts from January 1, 2019, to December 31, 2022. The research results were processed using panel data regression, the best model regression was random effect model. One independent variable, earnings management, was found not to significantly affect profitability. However, the study found that the level of tax avoidance has a positive and significant impact on company profitability. The size of the board of commissioners' independence as a moderating variable did not strengthen or weaken the independent variables simultaneously or partially against company profitability, but independence board of commissioners could significantly affect on profitability as independent variables. This is a quantitative research with hypothesis testing. The implications of this study state that there is a high tax aggressiveness in Indonesia due to the actions of multinational companies in global transactions, thus recommending that the government further evaluate current international tax policies.